TADCompare: An R Package for Differential and Temporal Analysis of Topologically Associated Domains - Cresswell, Kellen G.; Dozmorov, Mikhail G. (Frontiers in Genetics, 2020)
Recent research using chromatin conformation capture technologies, such as Hi-C, has demonstrated the importance of topologically associated domains (TADs). TADs are considered to be relatively stable three-dimensional (3D) genomic structures orchestrating gene expression regulation; yet, many dynamically reorganize during development or disease, and exhibit cell- and condition-specific differences. Quantification of the dynamic behavior of TADs will help to better understand genome regulation. Methods for comparing TADs between cells and conditions are highly limited. We developed TADCompare, a method for differential analysis of TAD boundaries between Hi-C datasets. TADCompare is based on a spectral clustering-derived measure called the eigenvector gap, which enables a loci-by-loci comparison of TAD boundary differences between datasets. Using this measure, we introduce methods for identifying differential and consensus TAD boundaries, and tracking TAD boundary changes over time. We further propose a novel framework for the systematic classification of TAD boundary changes. Colocalization- and gene enrichment analysis of different types of TAD boundary changes demonstrated distinct biological functionality associated with them. TADCompare is available on https://github.com/dozmorovlab/TADCompare and Bioconductor (submitted).